PERBANDINGAN COP AC SPLIT KAPASITAS 1 PK MENGGUNAKAN REFRIGERANT R410a DAN R32 DENGAN VARIASI KECEPATAN FAN EVAPORATOR - Kusnandar Kusnandar; Yudhy Kurniawan (Universitas Tridinanti Palembang, 2019)
Air Conditioning Split or AC Split is one of the air conditioning system that works by using a vapor compression system. The vapor compression system is one of the most cycles used for mechanical refrigeration systems, while the vapor refrigerant will be compressed by the compressor as the main component in addition to other components such as condensers, expansion valves and evaporators. This research focuses on AC Split Coefficient of Performance (COP) with Comparison of Refrigerants R410a and R32 with variations speed based on the Evaporator Fan speed. This analysis method uses two AC Split each capacity is 1PK with two different of refrigerants R32 and R410a, as well as varying in Low, Medium and High-level speed with air flow velocity in each mode respectively 1.2 m/s, 1.5 m/s and 1.9 m/s. From the result that COP on R410a refrigerant is 8.13 and COP on R32 refrigerant is 5.3. And also, the efficiency of R410a is 72.8% and R32 is 70.67%. So, AC Split with refrigerant R410a has better COP compared with AC Split with refrigerant R32. Keywords: COP, AC Split, Refrigerants, R410a, R32, Efficiency